1992
DOI: 10.1159/000288593
|View full text |Cite
|
Sign up to set email alerts
|

Fluvoxamine Treatment for Chronic PTSD: A Pilot Study

Abstract: A group of 24 Dutch World War II Resistance veterans with a documented traumatic war history and a (partially) positive diagnosis of current posttraumatic stress disorder (PTSD) was studied. This special group of war victims is characterised by chronicity, suffering from intractable posttraumatic complaints for decades. They were treated with fluvoxamine (Fevarin), a selective serotonin reuptake inhibitor with antidepressive and anxiolytic properties. The study was designed as an open-ended, outpatient pilot s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 9 publications
1
34
0
2
Order By: Relevance
“…Fluvoxamine ameliorated PTSD symptoms in a significant number of patients during a 12-week open study in 24 Dutch World War II Resistance veterans; anxiety levels and vital exhaustion also improved [De Boer et al, 1992].…”
Section: Treatment Options In Ptsdmentioning
confidence: 96%
“…Fluvoxamine ameliorated PTSD symptoms in a significant number of patients during a 12-week open study in 24 Dutch World War II Resistance veterans; anxiety levels and vital exhaustion also improved [De Boer et al, 1992].…”
Section: Treatment Options In Ptsdmentioning
confidence: 96%
“…Moreover, although there is evidence supporting the modest treatment response in combat-related compared to civilian PTSD (De Boer et al 1992 ;Marmar et al 1996 ;Zohar et al 2002), it has been shown that veterans from the general population, and not VA, achieve as much benefit from SSRI therapy as do non-veterans (Marshall et al 2001 ;Tucker et al 2001 ;Martenyi et al 2002a, b). There is also evidence indicating that, aside from acute-phase PTSD, flexibly dosed fluoxetine is also effective in the maintenance phase of the disease by sustaining improvements and preventing relapses (Martenyi & Soldatenkova, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four Dutch WW II resistance veterans with PTSD were prescribed¯uvox-amine for a period of 4 weeks in an open, uncontrolled study and found improvement in symptoms of survivor guilt, insomnia, nightmares, intrusive recollections, explosiveness and fear (de Boer et al, 1992). Conclusions which may be drawn from both the above studies (Boehnlein and Sparr, 1993;de Boer et al, 1992) are limited because of small numbers and lack of controls. War pensions for combat-related PTSD may be secured (Naval, Military and Air forces etc (Disablement and Death) Service Pensions Order 1983, 1984.…”
Section: Treatmentmentioning
confidence: 99%